Sonographic measurement of splenic length in children at Cipto Mangunkusumo Hospital - H F Wulandari; Kemas Firman (Paediatrica Indonesiana, 2005)
Objectives The aim of this study was to determine the 10 th and90 th percentiles and medians of normal splenic lengths of Indone-sian children at Cipto Mangunkusumo Hospital by ultrasonogra-phy using a method introduced by Rosenberg et al .Methods The maximum splenic length was obtained in longitudi-nal coronal plane with the splenic hilum visualized. The age of thepatients were recorded. The medians and 10 th and 90 th percen-tiles for each age group were determined.Results Sixty-nine boys and 46 girls were examined at our institu-tion. The youngest subject was one month old and the oldest was15 years old. The 10 th percentile, median, and 90 th percentilesplenic length in the 1-3 months age group were 3.421 cm, 3.795cm, and 4.343 cm, respectively. In the 3-6 month age group thesemeasurements were 3.689 cm, 4.29 cm, and 5.094 cm, respec-tively; in the 6-12 month age group 4.016 cm, 4.72 cm, and 5.366cm, respectively; in the 1-2 years age group 4.558 cm, 5.04 cm,and 5.502 cm, respectively; in the 2-4 year age group 5.151 cm,6.225 cm, and 6.816 cm, respectively; in the 4-6 year age group5.774 cm, 6.415 cm, and 7.82 cm, respectively; in the 6-8 year agegroup 6.077 cm, 7.505 cm, and 8.228 cm, respectively; in the 8-10years age group 6.354 cm, 7.77 cm, and 8.602 cm, respectively;in the 10-12 years age group 6.354 cm, 7.77 cm, and 8.602 cm,respectively; and in the 12-15 year age group 7.934 cm, 9 cm, and9.919 cm, respectively. In all age groups, the 10 th percentiles,medians, and 90 th percentiles were smaller than those of Ameri-can children as reported by Rosenberg et al.Conclusion The normal splenic lengths of Indonesian childrenare smaller than those of American children as reported byRosenberg et al.